Instructional Material Influence on Biology Students Academic Performance in Senior School in Ilorin West, Kwara State - ., Abidoye; Omosholape, Florence; Omotayo, Abidoye Adekunle; Olaide, Malik Sarat (VNU Journal of Science: Education Research; Vol 41 No 4DO - 10.25073/2588-1159/vnuer.4737, 2025)
This Study examined the influence of instructional material on Biology students’ academic performance in senior school in Ilorin West LGA, Kwara State. The negligence of the effective use of instructional materials and facilities in learning Biology by students has affected the successful performance of students in senior secondary schools across Nigeria. Three research questions were formulated while two hypotheses were tested for the study. The study was a descriptive research of the survey type. It was targeted at the Biology students in senior secondary schools in Ilorin West LGA, Kwara State, Nigeria. A random sampling technique was used to select 120 Biology students from senior secondary schools in Ilorin West LGA, Kwara State, Nigeria. A researched designed questionnaire was used to accumulate information from respondents. The data accumulated was analyzed using frequency count and percentage, mean and standard deviation while the research hypotheses were analyzed using an independent t- test to test the hypotheses 1 and 2. Findings from the study revealed that Biology instructional materials has a great influence on senior secondary students’ academic performance. The students taught with Biology instructional materials have excellent performance compared with those taught without. The findings shows that there was no significant based on gender while there was   significant influence based on school type. Recommendations made were that; Ministry of Education should take responsibility in providing Biology instructional materials to schools, all Biology teachers should make use of Biology instructional materials in the delivery of their lessons to the students to facilitate competition among the male and female students, government should provide public schools with Biology instructional materials to enhance better performance of students in Biology.